Public Relations Practices in Government Social Responsibility Communication and Institutional Image Construction - Ahmad, Seruni hi; Sumarlan, Iman (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
This study examines how public relations roles are enacted in Government Social Responsibility (GSR) communication activities—publicly framed as Corporate Social Responsibility (CSR)—and how these practices contribute to institutional image construction in a local government context. Adopting a qualitative interpretive design, the study was conducted at the Dinas Pemberdayaan Masyarakat Desa of Brebes Regency, Indonesia. Data were gathered through non-participant observation of GSR socialization meetings, in-depth interviews with public relations practitioners and community participants, and analysis of institutional documents. Analysis followed a systematic qualitative coding process, including open coding, focused coding, and analytical categorization, guided by public relations role theory as a sensitizing framework. The findings show that public relations roles are enacted as interactional practices rather than fixed organizational functions. Communication facilitation emerged through dialog management and adaptive explanation, expert prescriber roles through advisory input and mediation of community concerns, and technical roles through informational materials supporting interaction. These repeated encounters shaped stakeholder interpretations of accessibility, responsiveness, and consistency, which cumulatively contributed to institutional image construction. This study underscores the importance of interactional competence in public sector public relations and advances role theory by grounding role enactment in observable communicative practice.